More than BOLD: Dual‐spin populations create functional contrast. Issue 2 (18th August 2019) - Taylor, Amanda J.; Kim, Jung H.; Singh, Vimal; Halfen, Elizabeth J.; Pfeuffer, Josef; Ress, David
Abstract : Purpose: Functional MRI contrast has generally been associated with changes in transverse relaxivity caused by blood oxygen concentration, the so‐called blood oxygen level dependent contrast. However, this interpretation of fMRI contrast has been called into question by several recent experiments at high spatial resolution. Experiments were conducted to examine contrast dependencies that cannot be explained only by differences in relaxivity in a single‐spin population. Methods: Measurements of functional signal and contrast were obtained in human early visual cortex during a high‐contrast visual stimulation over a large range of TEs and for several flip angles. Small voxels (1.5 mm) were used to restrict the measurements to cortical gray matter in early visual areas identified using retinotopic mapping procedures. Results: Measurements were consistent with models that include 2 spin populations. The dominant population has a relatively short transverse lifetime that is strongly modulated by activation. However, functional contrast is also affected by volume changes between this short‐lived population and the longer‐lived population. Conclusion: Some of the previously observed "nonclassical" behaviors of functional contrast can be explained by these interacting dual‐spin populations.